Investment scenarios for rice R&D in LAC welfare and food security implications - Petsakos, Athanasios; Andrade, R; Rivera, T.; Schiek, B (2023)
Increasing annual investments from 225 to 260 million USD by 2050 is needed to sustain the yield growth implied by SSP2 (0.6% annually). If we want to reach 10t/ha (1.5% annual increase) investments must increase to 275 million USD annually by 2050. Targeting higher yields will mainly generate economic benefits for producers, but very limited benefits for consumers and for food security in LAC. These economic benefits in LAC can be attained if international trade is possible. When prioritizing R&D investments we need to identify broader impacts: who wins, who losses, and where.